P17 TIPS outcomes for Budd–Chiari: a single tertiary centre experience. (6th September 2011) - Macnaughtan, J; Hogan, B; Tritto, G; Mullan, M; Yu, D; Thorburn, D; O'Beirne, J; Jalan, R; Patch, D; Burroughs, A
Abstract : Introduction: TIPS insertion is an important intervention in the management of Budd–Chiari syndrome. We describe the experience of a single tertiary referral centre. Aim: The aims of this study were to describe the series of patients undergoing TIPS insertion for Budd–Chiari syndrome at the Royal Free Hospital, survival post-TIPS insertion and re-intervention rates. Method: A retrospective analysis of the Royal Free Hospital radiology database was conducted to identify all patients who underwent all TIPS procedures between January 1991 and January 2011. Patient records were used to subsequently identify those patients in whom Budd–Chiari was the principal indication for TIPS insertion and to characterise this patient cohort. Results: 1073 TIPS-related procedures were conducted at the Royal Free Hospital between January 1991 and January 2011. Of these, 51 patients underwent TIPS insertion for Budd–Chiari syndrome between January 1991 and January 2011 of which 61% (31/51) were female and 39% (20/51) were male. The mean age at the time of TIPS insertion was 40 years (±1.96). All patients were anticoagulated post procedure. 1-year transplant-free survival post-TIPS insertion was 93%. TIPS insertion could not be achieved in three patients. TIPS stenosis/occlusion was more common than in other TIPS indications. The mean number of TIPS-related interventions was 2.5 (1–10). Local thrombolysis with tissue plasminogen activator was required in three cases and patency/intervention rates were significantly improved with the addition of asprin to standard warfarin anticoagulation. No patients proceeded to liver transplantation. Regenerative nodules post TIPS were common on surveillance cross sectional imaging. Conclusion: Excellent 1-year transplant-free survival can be obtained in Budd–Chiari syndrome with TIPS placement. Patients are complex and may require multiple interventions and therefore probably best managed in experienced centres.